Satu Dekade Sejak Krisis Keuangan Global: Analisis Ekspor Perikanan Indonesia dan Pertumbuhan Ekonomi Sektoral - Ronaldo Johanis Gontung; Peri Akbar Manaf (Jurnal Syntax Transformation, 2021)
This paper examined the relationship of fishery trade, foreign direct investment (FDI), and sectoral economic growth in Indonesia since the global financial crisis, using quarterly time series data from 2008 to 2018. It is based on the secondary sources of data were collected from Central Bank of Indonesia, Central Bureau of Statistics, and International Trade Center. The ordinary least square regression has been used by the authors to find out the linkages of fishery export to those variables. Furthermore, in this study, the regression results confirmed that there was a positive relationship between exports and GDP of the fisheries sector, it was also found that Indonesian fishery exports were relatively at a positive level despite the global financial crisis.